Consumer Acceptance towards Renewable Energy Transition - Majhi, Ritanjali; Banerjee, Aneesha (Journal of Environmental Accounting and Management, 2026)
The transition of non-renewable to renewable energy has always been a matter of concern for the development of a sustainable environment. As climate change and pollution are affecting the habitat, it is the dire need of the situation that some changes should be incorporated. Different stakeholders may not possess the same outlook and level of acceptability towards it, but it is the prime concernof the moment. This paper studies energy consumers ‘attitude towards the transition to renewable energy in their daily life and the constraints preventing them from it. Respondent completed questionnaires which show a strong will and awareness about the rising concern of environmental change and people already have energy conservation attitude. In the ﬁrst phase, we have analyzed the relative importance of the household practices and the conservation pattern. Whereas, in the next, we have studied the demographic and behavioral factors resulting in these habits. The output which generated shows that the consumers are interested in conservation techniques and are taking measures for adapting it. They showed relevant interests in the cultivation of renewable energy and concern toward environmental hazards generated due to fossil fuels. It is also seen that based on their lifestyle and educational background the consumption pattern varies and moreover it can be said that different people have a different outlook towards it. People belonging to the higher education group (Cluster 1, 115 people) are more adaptive towards the renewable energy transitions rather than, the lower educational group (Cluster 3, 41 people) where they are resistive towards the changes. The survey was done in an Indian concept and policy makers can utilize the ﬁndings to incorporate changes and build awareness among the residents.